A grain based modeling study of fracture branching during compression tests in granites. (July 2015) - Hofmann, Hannes; Babadagli, Tayfun; Zimmermann, Günter
Abstract: In a previous study we used a the grain based modeling approach (GBM) to carry out a sensitivity analysis of mineral size and random distribution of minerals and particles and their influence on elastic properties, strength and fracture types in Aue Granite. In the present study, the same calibrated model is used to further evaluate the influence of these parameters as well as the particle, parallel-bond, and smooth joints properties of the model on the resulting fracture patterns. It was found that complex crack networks always develop in heterogeneous GBMs, and crack network complexity increases with increasing heterogeneity. While each of the particles, parallel bond, and smooth joint properties govern the development of a specific crack type, no obvious relations between these properties and the total number of cracks and the resulting crack network complexity were found. Highlights: Fracture branching in GBM is governed by heterogeneities and model discretization. Heterogeneous GBMs always develop complex fracture networks in compression tests. Relative amounts of cracks are independent of model size and mineralogy. Fracture complexity increases with increasing heterogeneity. Micro properties govern development of specific crack types.